2017
DOI: 10.1111/epi.13854
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term applicability of the new ILAE definition of epilepsy. Results from the PROLONG study

Abstract: Our results support the applicability of the new epilepsy definition in clinical practice. Individual patient characteristics and a personalized diagnostic approach can justify treatment after a single unprovoked seizure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 20 publications
2
25
0
1
Order By: Relevance
“…In principle, the diagnosis was made after two or more unprovoked seizures occurring more than a day apart, or a single unprovoked seizure in the presence of risk factors or investigations suggesting a high risk of recurrence including an epileptiform abnormality on electroencephalography (EEG), an epileptogenic lesion on neuroimaging, or remote symptomatic aetiology. This approach is consistent with definitions later published by the International League Against Epilepsy (ILAE) in 2005 and 2014 that have been subsequently validated for patients with a single seizure at diagnosis …”
Section: Methodssupporting
confidence: 82%
See 1 more Smart Citation
“…In principle, the diagnosis was made after two or more unprovoked seizures occurring more than a day apart, or a single unprovoked seizure in the presence of risk factors or investigations suggesting a high risk of recurrence including an epileptiform abnormality on electroencephalography (EEG), an epileptogenic lesion on neuroimaging, or remote symptomatic aetiology. This approach is consistent with definitions later published by the International League Against Epilepsy (ILAE) in 2005 and 2014 that have been subsequently validated for patients with a single seizure at diagnosis …”
Section: Methodssupporting
confidence: 82%
“…2014 14 that have been subsequently validated for patients with a single seizure at diagnosis. 15 Patients were classified as untreated if they had not been commenced on ASM therapy, regardless of whether treatment was recommended or declined. The presence or absence of neuroimaging lesions considered to be epileptogenic, 16,17 and epileptiform abnormalities on EEG, 18 were documented.…”
Section: Key Pointmentioning
confidence: 99%
“…The most important strengths are the large sample size, the long follow-up, and the accuracy of the diagnosis and treatment of epilepsy. Moreover, the long-term applicability of the new ILAE definition of epilepsy has been shown using this cohort 23. The main limitations are the retrospective design and the unstructured data collection by the caring physicians.…”
Section: Discussionmentioning
confidence: 96%
“…This study showed a recurrence risk of seizures of 83.6% at 10 years for those diagnosed using the new definition. 14 The recurrence risk using the old definition was 57% at 1 year and 73% at 4 years according to a paper published by Hauser et al 15 Based on the results of the study by Beretta et al, it is clear that not diagnosing individuals with epilepsy after their first seizure who had an abnormal study (e.g., EEG, MRI, computed tomography [CT]) was doing them a disservice. The delay in diagnosis of epilepsy resulted in (1) patient noncompliance with seizure medications due to lack of appreciation for the likelihood of having another seizure and 2clinician's failure to treat.…”
Section: Definitionsmentioning
confidence: 99%